Abandoned housing project in Malaysia - Mohamed, Izamudin (2014)
Malaysia has made great strides in meeting the requirements of its citizens in relation to housing. Concerning the production of housing in Malaysia, the private developers are allowed to houses in development areas which have been identified by local authorities for housing development. The house construction has become significant contributor to construction industry. However, housing sector is also facing several issues such as delay, poor workmanship and abandoned projects. Nevertheless, the existence of abandoned housing projects in Malaysia where the house buyers have suffered has jeopardised the housing industry and contributed to the housing industry problem. This study analyses the state of abandoned housing projects in Malaysia include the causes, socio-economic impacts and policy remedies to prevent the abandoned housing projects. The result shows that the developers are the main party that contributed to abandoned housing project due to the financial problems. The survey reveals that the abandoned housing projects have greater impact on social issues compared to the economic aspect. Tightening the procedures for issuance of housing development licenses and focusing on a developer's financial capacity is the best policy remedy to prevent the abandoned housing project in Malaysia